SEJARAH DAN DINAMIKA PEMBAHARUAN LEMBAGA PENDIDIKAN ISLAM DI NUSANTARA: SURAU, PESANTREN DAN MADRASAH - Ruri Albersa; Roganda; Fauza Masyhudi (Journal of International Multidisciplinary Research, 2023)
The purpose of this writing is to find out the history of the dynamics of renewal of Islamic educational institutions in the archipelago, namely surau, Islamic boarding schools and madrasas in the history of Islamic education. The Indonesian Islamic community must pay attention to the development of Islam, the history of education from time to time, from the time of the Prophet Muhammad, friends of Khulafaurrasyidin, Tabi', Tabiuttabi'in to the present day. History teaches us to look at the development of education that we have gone through so that it can be used as an evaluation and education for us and future generations. The Muslim community deserves to forget and avoid history, with history we learn to understand education in the past, provide analytical skills, appreciate the services of previous people, know technological developments and knowledge of studying the mistakes of the education system in the past so as not to repeat mistakes again, history also has an important role in formation of national identity and personality and religion. However, in this day and age, many students of science are not interested in knowing the history of the development of education, focusing on the relevance of the formation process of Suarau education, Islamic boarding school, Islamic boarding school, how the meaning of Suarau, Islamic boarding school, madrasah, the history of emergence, and the education system, and the progress and decline of Surau, Islamic boarding school are the same in the modern era. modern technological sophistication